An overview of thrombotic complications of old and new anticancer drugs - Levi, Marcel; Sivapalaratnam, Suthesh (Thrombosis research, 2020)
Thrombosis is a common complication of cancer with a mean prevalence of 15%. Most commonly, this presents as venous thromboembolism; however, other manifestations such as arterial thrombosis or thrombotic microangiopathy may occur. Cancer itself is not only associated with risk factors for thrombotic complications, including intrinsic biological effect of malignant cells, accompanying operations, or the presence of indwellingvascular catheters, but there is also an additional risk caused by anticancer agents including chemotherapy and immunotherapy. In most cases the underlying pathogenetic factor that contributes to the thrombotic risk associated with chemotherapy is endothelial cell injury (or loss of protection of endothelial integrity, for example by vascular endothelial growth factor inhibition). In addition, individual anticancer agents may have specific prothrombotic effects. As in recent years more intense anticancer drugs are administered, such as in myeloablative conditioning regimens preceding stem cell transplantation, thrombosis and in particular thrombotic microangiopathy are a more frequent complication in anticancer treatment.